Drafting a realistic tourism policy: the airlines’ strategic influence - Liasidou, Sotiroula (My University, 2017)
Purpose: In tourism literature, policy is synonymous with the involvement of the government in terms of planning, developing and organising the destination. In the case of the airline industry, policy is verified by a supranational body, the European Union, which sets outs guidelines for all member states. This paper aims to examine how the tourism policy and planning in Cyprus is formulated in an attempt to understand the strategic response of the airlines in the way they fulfil the aims of the tourism strategy. Design/methodology/approach: The primary data are based on the results of 25 semi-structured, in-depth interviews with powerful and elite tourism and airline decision makers in Cyprus. Findings: The results of the research suggest that the tourism policy should take into more consideration and develop strategic synergies and have tighter links with airlines companies in terms of planning and policy formation. This will enable the destination and the government to provide more realistic targets in tourism policies especially in islands. The airline network can both increase the number of arrival and diversify the demand all year round and offer more economic opportunities. Originality/value: The study addresses two important aspects in terms of tourism development. The first is the policy initiative and the second is the role of the airlines’ for the purpose of tourism. Interrelation between tourism policies and airline developments are rather neglected in the tourism literature. Thus, this study highlights the point that in destination planning especially on islands, the airline decision-makers should participate in the policy making process and set more realistic targets. Additionally, airlines play an important role for destinations reaching numerical targets.
Keywords: Airline strategies; Cyprus; LCCs; Semi-structured interviews; Tourism policy